Development and Pilot Implementation of a Training Framework to Prepare and Integrate Pharmacy Students into a Multicentre Hospital Research Study - Aaron Noble; Rachael Raleigh; Amy Page; H. Laetitia Hattingh (MDPI AG, 2022)
A unique approach was introduced to integrate pharmacy students into a multicentre patient-centred research project predicting medication related harm (MRH) post-discharge. A training framework was developed to prepare students for research participation and integration. The framework aligned research project tasks with the pharmacists' national competency standards framework. The framework was piloted on four research placement students from two local universities during three hospital placements, from October 2020 to August 2021. Following their initial orientation and training, students collected data from 38 patients and were involved in patient screening processes, interviewing, data collection and analysis. Patients' MRH risk scores correlated with re-admission rates with 16/38 (42%) of patients re-admitted within eight weeks following discharge. Their participation in the research enabled students to obtain skills in (1) literature searching, (2) maintaining patient confidentiality, (3) interviewing patients, (4) obtaining data from medical records, (5) communicating with patients and clinicians, and (6) the use of clinical information to predict MRH risk.